2020
DOI: 10.3389/fimmu.2020.00365
|View full text |Cite
|
Sign up to set email alerts
|

A20 Restricts Inflammatory Response and Desensitizes Gingival Keratinocytes to Apoptosis

Abstract: The pathophysiology of periodontal disease involves a perturbed immune system to a dysbiotic microflora leading to unrestrained inflammation, collateral tissue damage, and various systemic complications. Gingival epithelial cells function as an important part of immunity to restrict microbial invasion and orchestrate the subsequent innate responses. A20 (TNFAIP3), an ubiquitin-editing enzyme, is one of the key regulators of inflammation and cell death in numerous tissues including gastrointestinal tract, skin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…In the oral mucosa, the stringent regulation of immune cell life span and turnover is an important dimension of immune homeostasis, and a disruption of apoptosis can contribute to chronic inflammation seen in periodontitis (Meghil and Cutler 2020). In fact, insufficient A20 levels sensitize gingival keratinocytes to bacteria and TNF-induced apoptosis, supporting the notion that A20-targeted therapies can help maintain the integrity of the gingival epithelium and restore impaired periodontal tissue homeostasis (Li et al 2020).…”
Section: A20 In Health and Diseasesmentioning
confidence: 71%
See 2 more Smart Citations
“…In the oral mucosa, the stringent regulation of immune cell life span and turnover is an important dimension of immune homeostasis, and a disruption of apoptosis can contribute to chronic inflammation seen in periodontitis (Meghil and Cutler 2020). In fact, insufficient A20 levels sensitize gingival keratinocytes to bacteria and TNF-induced apoptosis, supporting the notion that A20-targeted therapies can help maintain the integrity of the gingival epithelium and restore impaired periodontal tissue homeostasis (Li et al 2020).…”
Section: A20 In Health and Diseasesmentioning
confidence: 71%
“…In support of plausible biological functions of A20 in promoting oral cavity health, A20 has been specifically shown to regulate inflammation, autophagy, and cell death responses in the oral mucosa (Hong et al 2016; Crump et al 2017; Li et al 2019; 2020; Yan et al 2020). A20 insufficiency was associated with a more severe disease phenotype in a murine periodontitis model (Li et al 2019).…”
Section: Insights For A20 Function In the Oral Cavitymentioning
confidence: 96%
See 1 more Smart Citation
“…Still, in mice infected with Porphyromonas gingivalis, bone marrow-derived macrophages from A20-deficient showed increased NF-kB activity and cytokine production compared with cells isolated from A20-competent mice (84). Recently, Li et al (85) in 2020 reported a specific role of an ubiquitin editing molecule in gingival keratinocyte inflammatory response, indicated that sufficient A20 levels is a major determinant to control apoptosis in response to microbial and inflammatory injury. Also, the A20 expression in response to oral bacterial depends among different cells and, therefore, it is essential studying the cell-type specific A20 responses and their effect on disease phenotype to develop targeted therapies (85).…”
Section: Studies On Ups In Human Periodontal and Oral Cell Lineagesmentioning
confidence: 99%
“…Recently, Li et al (85) in 2020 reported a specific role of an ubiquitin editing molecule in gingival keratinocyte inflammatory response, indicated that sufficient A20 levels is a major determinant to control apoptosis in response to microbial and inflammatory injury. Also, the A20 expression in response to oral bacterial depends among different cells and, therefore, it is essential studying the cell-type specific A20 responses and their effect on disease phenotype to develop targeted therapies (85). Another mechanism that could explain the ability of transforming growth factor β (TGFβ) to inhibit Toll-like receptor (TLR)-NFκB signaling is protein arginine methyltransferase 1 (PRMT1)-induced Smad6 methylation.…”
Section: Studies On Ups In Human Periodontal and Oral Cell Lineagesmentioning
confidence: 99%